Morphological Bias of Ancient Artifacts: A Case Study of Incense Burners in Ming and Qing Dynasties. (30th November 2021) - Chen, Yu-Fu; Wei, Jie
Abstract : This study verifies the relevance of the combination of traditional Chinese artifacts and perceptual semantic research. It provides new research ideas to study the Chinese artifact culture. Moreover, it helps people to understand the cultural spirit better and design crystallization of traditional artifacts. This study considered Chinese traditional incense burners in Ming and Qing dynasties to adopt morphological analysis and affinity diagram to select representative experimental samples. Furthermore, this research applied the perceptual engineering theory to explore the relation between design group's description of perceptual semantics and the shape of incense burners. The focuses were the design group on the shape and style of ancient artifacts in aesthetic consideration. According to the results of semantic principal component analysis, the perceptual semantic bias of the design group towards incense burners was concentrated, which is related to the style acceptance of incense burners. Among these related incense burner styles, the design group paid more attention to the proportional design of "incense burner foot" in the perceptual bias of incense burner shape and preferred the proportional incense burner shape of "long foot."